Implementation the Islamic Artistic Expressionism to Islamic Culture Center Design in Banda Aceh - Nurul Aulia (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2018)
Islamic Culture Center / Islamic Center is a religious institution that is the center of Islamic development and development that acts as a pulpit of the implementation of da'wah in the era of national development [1]. This building facilitates the field of Worship, general and religious education, community service, and Islamic art that can serve as the implementation of da'wah, especially in the city of Banda Aceh. In presenting the nuances of Islamic culture in this building, then the selection of appropriate themes is very important. This can in addition be a driving force for building users because of the beauty of the architecture, the selection of the right theme is also a separate identity for the building. Therefore, the design of this Islamic Cultural Center adopted the theme of "Islamic Artistic Expressionism" with the approach of Islamic Architecture. Implementation of Islamic architecture concept on this design not only from the form of the building but also on the design of the landscape. In addition, the application of Islamic values is also seen in the mass order of buildings, relationships between buildings, and the preservation of nature as taught in the Qur'an and Sunnah of the Prophet.